THE COMBINED EFFECT EMPLOYEE ENGAGEMENT AND STRATEGIC CLARITY IN STRATEGIC SUCCESS: AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF LEADERS WORKING IN PRIVATE UNIVERSITIES IN THE MIDDLE EUPHRATES (World Bulletin of Social Sciences, 2023)
The current study tests the correlation and influence relationship between employee engagement that include (Physical engagement, knowledge engagement, emotional engagement) and strategic clarity (Clarity of activities and procedures, clarity of objectives, clarity of use of resources, clarity of the role of employees, clarity of the organizational structure) And its impact on the strategic success dimensions((survival, adaptation, growth and, learning), from which two main hypotheses following with four subhypotheses
Keywords: employee engagement; strategic clarity; strategic success